Posted by **Tom** on Monday, February 23, 2009 at 7:47pm.

Let f(x) = (lne^2x)/(x-1) for x>1. If g(x) is the inverse of f(x0, then g'(3) = ?

A. 2

B. 1

C. o

D. -1

or E. -2

if you can show/explain how to get that please, thanks

## Answer This Question

## Related Questions

- Math - Logarithms - Could you please explain why lne^2 = 2, e^lne^2 = e^2, e^...
- Calculus - please check my work - evaluate rounding to 2 decimal places if ...
- Math - Inverse Functions - Find the inverses of the following functions. y = 3(x...
- algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...
- College Algebra - Find the inverse of the function below. Graph the function ...
- math - The cost of producing q articles is given by the function C=f(q)=100+2q...
- Math - Directions: Does the following inverse of [2 6 exist? 1 3] If it isn't an...
- Calculus - F(x) = 1-x and g(x) = 1/x These functions have the property that f = ...
- algebra - Given f(x)=x^2+4 and g(x)=3x+1 simplify g^-1(x)(inverse) plaese show ...
- Maths B - (a) What is the inverse of the function y = 3x2 ? (b) On the same set ...

More Related Questions